STRATEGI PEMASARAN DIGITAL, CITRA MERK, DAN LOYALITAS PELANGGAN TERHADAP PRODUK FASHION DI E-COMMARCE LAZADA - Rista, Nur; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This research investigates digital marketing strategies, brand image, and customer loyalty towards fashion products on Lazada e-commerce, a leading e-commerce platform in Indonesia. Researchers use a qualitative descriptive approach and literature study, a method of writing literature reviews from online applications such as Mendeley, Google Scholar and other online scientific applications. The aim of this research is to explain the importance of brand image for companies in business competition, to find out the level of brand image awareness among consumers so that they become loyal to the company and the products offered. Lazada, as one of the leading e-commerce platforms in Indonesia, faces major challenges in adapting and innovating their inventory marketing strategy to remain competitive.